Designing Pilot Projects as Boundary Objects A Brazilian Case Study in the Promotion of Sustainable Design - Zurlo, Francesco; Nunes, Viviane dos Guimarães Alvim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes a collaborative Design Pilot Project held in Brazil (called MODU.Lares) involving micro and small enterprises and other actors in the furniture sector. The experience was based on an action research method and evaluated by using a tool, in order to assess the value of pilot project as a boundary object capable of fostering innovation and sustainability. The impact of the Design Pilot Project in triggering change in a fragmented local system with a poor environmental and social record, as well as management and innovation issues, were assessed with the help of the same tool, taking into account environmental, technological, economic, sociocultural, and organizational indicators. The collaborative network established was chiefly based on four elements: prototypes, meetings, exhibitions and the Pilot Project (as an overall process). The results indeed demonstrate that a Design Pilot Project can be a valid instrument for establishing a collaborative environment that promotes sustainability and innovation, particularly in contexts with a weak associative culture. Such collaborative projects can constitute the first step in a design policy cycle in developing countries, contributing to the definition of ideas and objectives among local stakeholders, minimizing the risks of failure, and increasing the chances of receiving governmental support.
Introduction -- Research Design -- The MP Assessment tool -- Theoretical Background -- Inter-Organizational Collaborative Network (ICoN) Model -- Design and the Furniture Industry in Brazil -- The context of intervention in Brazil -- Design Pilot Project Strategy -- Research Findings -- Final Recommendations.
Keywords: Engineering design; Technological innovations; Sustainability; Engineering Design; Innovation and Technology Management; Sustainability